Contested Conversions to Islam - Krstić, Tijana.
1 online resource (281 pages)
Keywords: This book explores the role of conversion to Islam in the emergence of the Ottoman Empire, its imperial ideology and Sunni identity, and its relationship with its Muslim and non-Muslim subjects, in the context of the early modern Mediterranean.